Organizacja pracy w pracowniczo-studenckim zespole projektowym - studium przypadku - Sobieski, Ścibór (Organization of work in working-student project group-case study, 2006)
The article describes organization of group which created software on requirements of central administrations of University of Lodz. This group consists students and academic employes. This fact, as well as specificity of environment, in which it run, have caused necessity of other look on management of such development group. We try to show in this article advantages of such approaches and we discuss problems that arose during our work.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 265-271